Interpreting the API: A Comment and Extension. - Barefield, Russell M.; Foster III, Taylor W.; Vickrey, Don (The Accounting Review, 1976)
The article presents a comment on the interpretation of API. In "Interpreting the API," Ronald M. Marshall concludes that API does not always provide a proper measure of either the private value of accounting data or the association between unexpected accounting signals and unexpected market returns. In addition, Marshall concludes that an alternative formulation of API always produces measures of these attributes, which are at least as good as those obtained via API. On the basis of these conclusions, Marshall argues that API constitutes the more appropriate tool for use in accounting research. Authors do not disagree with Marshall's conclusions from a conceptual viewpoint, but they do question the desirability of using API in accounting research because of its inherent subjectivity and costliness in terms of time. Since API does not possess these defects, authors believe that it constitutes the better research technique when, conceptually speaking, it can be expected to yield results, which are equivalent to those that would be produced using API. One objective of the paper is to identify an important sufficient condition, under which the two API will produce equivalent results.